Chapter 6: Ethnic diversity, social networks, and the social resilience of schools - Kroneberg, Clemens (Edward Elgar Publishing, 2022)
By promoting shared feelings of belonging and positive intergroup relations, schools can strengthen the social resilience of ethnically diverse societies. This chapter discusses how social networks can both enable and constrain schools in serving this function. Research has shown that residential segregation and segregated parental networks contribute to ethnic segregation across schools, which tends to widen educational inequality and erects barriers for inter-group contact. Even in ethnically mixed schools, however, studies have repeatedly found evidence for ethnic segregation and ethnic homophily in the social networks of students. This has been argued to potentially undermine social resilience by hindering the reduction of inter-ethnic prejudice, triggering feelings of threat or superiority, or increasing the likelihood of victimization by out-group members. The chapter critically evaluates these claims, points out promising interventions, and identifies open questions for future research.